2019
DOI: 10.3390/electronics8030283
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Virtual Machine Placement Based on Grey Wolf Optimization

Abstract: Virtual machine placement (VMP) optimization is a crucial task in the field of cloud computing. VMP optimization has a substantial impact on the energy efficiency of data centers, as it reduces the number of active physical servers, thereby reducing the power consumption. In this paper, a computational intelligence technique is applied to address the problem of VMP optimization. The problem is formulated as a minimization problem in which the objective is to reduce the number of active hosts and the power cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 44 publications
(76 reference statements)
0
17
0
Order By: Relevance
“…Equations ( 6) and ( 7) relate to CPU and memory utilization respectively that must not exceed the value of capacity constraints (Pi). e power consumption of active PM without load is approximately 50% to 70% of fully utilized PM [32]. erefore, turning off inactive PMs are essential to decrease the total power consumption of a cloud data center.…”
Section: Objective Functionmentioning
confidence: 99%
“…Equations ( 6) and ( 7) relate to CPU and memory utilization respectively that must not exceed the value of capacity constraints (Pi). e power consumption of active PM without load is approximately 50% to 70% of fully utilized PM [32]. erefore, turning off inactive PMs are essential to decrease the total power consumption of a cloud data center.…”
Section: Objective Functionmentioning
confidence: 99%
“…Simulated experiments showed that the algorithm has better scheduling effect. Al-Moalmi et al [ 32 ] proposed the use of the GWA for the optimization of virtual machine layout, which can reduce the number and energy of active hosts. Experiments showed that using this algorithm can effectively reduce energy consumption and use CPU and memory resources better.…”
Section: Related Workmentioning
confidence: 99%
“…In [20] the authors adopt grey wolf optimizer to solve VM optimization into an optimum number of active hosts. As a result of submitting the VMs to the minimum number of PMs, the power consumption had been reduced to the minimum.…”
Section: Related Workmentioning
confidence: 99%